ChemInform Abstract: Palladium‐Catalyzed Divergent Arylation with Triazolopyridines: One‐Pot Synthesis of 6‐Aryl‐2‐α‐styrylpyridines. Issue 30 (July 2016) - Moon, Youngtaek; Kwon, Soonhyung; Kang, Dahye; Im, Honggu; Hong, Sungwoo
Abstract: The title pyridines are successfully prepared by two different catalytic arylations performed in one‐pot with a single Pd catalyst using two different bases.